2 - 4N = 2 + 3N
Subtract 2 from each side:
-4N = 3N
Add 4N to each side:
0 = 7N
N = 0
That's the only value of ' N ' for which the given equation
can become a true statement.
10n+2
3 + 3n = 9 + 2n + 4n n = -2
3n+1=7 3*2+1=7
22n + 2.
3925
10n+2
7n - 2 + 3n + 4 = 7n + 3n - 2 + 4 = 10n + 2 which can be simplified to 2(5n +1)
3 + 3n = 9 + 2n + 4n n = -2
4n
3n+1=7 3*2+1=7
3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (4) = 3n + 6
5-2=3n=3
3n+2+3n+2=6n+4
4n-8=3n+2 4n=3n+2+8 4n=3n+10 4n-3n+10 n=10 N = 10
3n+6=18 n+2=6 n=4
22n + 2.
The answer to -2(4+3n)=24 is:-5.33